Design of Secure and Efficient Framework for Vehicular Digital Twin Networks Using ECC - Vinod Kumar; Fauzia Hassan; Anil Kumar Nishad; Ramakant Prasad; Pooja Gupta; Mohammad Amir; Furkan Ahmad (IEEE Access)
Digital twins (DT) are digital copies of tangible assets and operations utilised in some industries to improve efficiency and foster creativity, accuracy, and decision making. Although beneficial, they have brought up some of the most critical security issues due to the complexity of their implementation and how they are incorporated into strategic systems. In this study, the security aspects of DTs that deal with challenges relating to data integrity, privacy, and secrecy are covered: potential vulnerabilities. For example, data used for malicious reasons, gaining unauthorised access, and interference with authorised network activities are considered in the planned attempt. In this study, the authors provide a secure and efficient protocol based on elliptic curve cryptography (ECC) to address security, privacy, and associated concerns in vehicular digital twins (VDT) networks. In addition, the paper discusses formal and informal security analysis based on the random oracle model, Burrows-Abadi Needham (BAN) logic, and Scyther verification tool. The proposed protocol ensures security, privacy, and other related security attacks and attributes in VDT networks. Furthermore, in the performance analysis section, we compare the communication and computation costs of the proposed protocol and related protocols. The proposed framework is secure and efficient in VDT network systems. Our analysis shows that the proposed protocol may apply to future VDT networks.